2008
DOI: 10.1002/app.28409
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of modified polystyrene with maleic anhydride in the presence of different solvents

Abstract: Polystyrenes (PS's) with different molecular weights were chemically modified with maleic anhydride (MA) with of benzoyl peroxide as an initiator or with a cationic catalyst such as FeCl 3 in chloroform. The effect of the solvents (i.e.; chloroform, benzene, toluene, xylene, and tetrahydrofuran), PS and MA concentration, molecular weight of PS, and type of catalyst used in the chemical modification was studied. The rate of the reaction was different with different solvents because of chain transfer to the solv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Different grafting behaviors were observed for the two halogenated solvents because of the different radical chain‐transfer constants of dichloromethane (0.15)19, 34 and chloroform (0.5) 35. A previous report showed that a solvent with a low chain‐transfer constant could slow down the chain growth and chain‐termination processes, which could eventually increase DOG 36–38. From Figure 1, chloroform was a suitable solvent at a VBC concentration of 50% or lower, whereas dichloromethane was a good solvent at a VBC concentration of 60%.…”
Section: Resultsmentioning
confidence: 85%
“…Different grafting behaviors were observed for the two halogenated solvents because of the different radical chain‐transfer constants of dichloromethane (0.15)19, 34 and chloroform (0.5) 35. A previous report showed that a solvent with a low chain‐transfer constant could slow down the chain growth and chain‐termination processes, which could eventually increase DOG 36–38. From Figure 1, chloroform was a suitable solvent at a VBC concentration of 50% or lower, whereas dichloromethane was a good solvent at a VBC concentration of 60%.…”
Section: Resultsmentioning
confidence: 85%
“…During recent years, polymer chemists have increasingly focused on the need to maximize efficacy because of the widespread use of polymers in high physicomechanical materials and the interest in improving their performance, adhesion, and photosensitivity. Chemical modification has great importance because of the impossibility of polymerization of the modified polymers with proper monomers (Wafaa, 2008). Modification reactions of polymers can be accomplished by use of a number of different reagents, like epichlorohydrin, organic anhydrides in the various reaction conditions or by the characteristic reactions such as alkylation, halogenation, nitration and sulfonation (Gibson, 1980;Kurbanova et al, 1979;1976;Seymour and Carraher, 1988).…”
Section: Introductionmentioning
confidence: 97%
“…Modification reactions of polymers can be accomplished by use of a number of different reagents, like epichlorohydrin, organic anhydrides in the various reaction conditions or by the characteristic reactions such as alkylation, halogenation, nitration and sulfonation (Gibson, 1980;Kurbanova et al, 1979;1976;Seymour and Carraher, 1988). The use of polymer materials, especially polymers with polyfunctional groups, has increased because of the demand of modern techniques with chemical modification (Wafaa, 2008). PS without additional functional groups has limited some properties such as thermal stability, mechanical strength, adhesion capability, corrosion resistance and photosensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…3 However, PS without additional functional groups has limited properties such as thermal stability, mechanical strength, adhesion capability, corrosion resistance, and photosensitivity. Accordingly, it has become a promising material for various applications in the automotive, electronics, and packaging industries, too.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Aside from its wide use in industrial applications, PS is also used for the production of plastic materials, which are used instead of metals in technology. 3 However, PS without additional functional groups has limited properties such as thermal stability, mechanical strength, adhesion capability, corrosion resistance, and photosensitivity. The undesired properties of PS can be improved with different reagents using modification reactions.…”
Section: Introductionmentioning
confidence: 99%